1991
DOI: 10.2466/pr0.1991.68.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Mmpi Differences among Mexican-American Male and Female Psychiatric Inpatients

Abstract: The purpose of this study was to examine to what extent Mexican-American male and female psychiatric patients, who share similar DSM-III--R diagnoses, differ on the MMPI. Differences were found on the Infrequency, Masculinity-Femininity, and Paranoia scales, with the 39 men obtaining significantly higher scores than the 21 women. These results, while suggesting possible differences in the phenomenology of depression, also suggest that MMPI differences between Mexican-American men and women may be reflective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, there was no statistically significant difference between NLWs and Latinxs with regard to falling into not under-reporting and possible under-reporting, and a score of less than 60 on the K-r scores suggests no evidence of under-reporting. Research examining K/K-r endorsement has mixed findings; while some studies have shown ethnic differences (McCreary & Padilla, 1977; Velasquez et al, 1991; Whitworth & McBlaine, 1993), others have failed to find ethnic differences on the K scale (McGill, 1980; Whitworth & Unterbrink, 1994). The status of ethnic differences on K-r remain equivocal as the results of the current study indicated that although there was a difference between the mean score for Latinxs and the mean score for NLWs, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no statistically significant difference between NLWs and Latinxs with regard to falling into not under-reporting and possible under-reporting, and a score of less than 60 on the K-r scores suggests no evidence of under-reporting. Research examining K/K-r endorsement has mixed findings; while some studies have shown ethnic differences (McCreary & Padilla, 1977; Velasquez et al, 1991; Whitworth & McBlaine, 1993), others have failed to find ethnic differences on the K scale (McGill, 1980; Whitworth & Unterbrink, 1994). The status of ethnic differences on K-r remain equivocal as the results of the current study indicated that although there was a difference between the mean score for Latinxs and the mean score for NLWs, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A higher proportion of Latinxs fell into the “possible over-reporting category” than NLWs. Research (McGill, 1980; Scott et al, 2009; Velasquez et al, 1991; Whitworth, 1988; Whitworth & McBlaine, 1993; Whitworth & Unterbrink, 1994) has consistently highlighted that Latinxs elevate the L/L-r scale. This literature parallels the results obtained regarding the L-r scale by the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, proportionate representation in sampling continues to be the regular practice in psychometrics-meaning that Mexican Americans are sampled per their representation in the general population, which results in the maintenance of previously established norms. Velasquez, Callahan, and Carrillo (1991) compared MMPI differences between Mexican American men and women. To correct some of the discrepancy in knowledge regarding Mexican Americans and personality assessment, researchers such as Roberto Velasquez and his colleagues have completed multiple studies evaluating the between-group differences among Mexican American and African American adolescents (Gomez, Johnson, Davis, & Velasquez, 2000); Latin American populations, Mexicans, and Latino college students (Boscan et al, 2000;Cabiya et al, 2000); Central American and Mexican immigrants (Clark, Callahan, Lichtszajn, & Velasquez, 1996); and, of course, between Latino and White outcomes on the MMPI-2 (Velasquez, Callahan, & Young, 1993).…”
Section: Renorming/restandardizationmentioning
confidence: 99%
“…The second approach involves the comparison of Hispanics with other Hispanics on a given psychological test (e.g., Pando, 1974;Quiroga, 1972;Velasquez, 1987;Velasquez, Callahan, & Carrillo, 1989, 1991Velasquez & Gimenez, 1987). The advantage of this approach is that it takes into account Hispanic's intracultural variation.…”
Section: Research Designs Most Frequently Used In Hispanic Clinical T...mentioning
confidence: 99%